Foot index: is it a tool for gender determination among Nepalese population? - Mansur, Dil Islam; Karki, Raj Kumar; Shrestha, Pragya; Mehta, Dilip Kumar; Maskey, Sunima; Dahal, Shreya (Journal of Chitwan Medical College, 2020)
Background: The human foot shows variations in its dimensions and shape in different age group of both male and female. It can be used as gender predictor of an individual in forensic science investigations which may have a great value for identification of unknown deceased body. This study was aimed to measure the various dimensions of foot and derive a tool to predict gender of an individual. Methods: This study was the cross-sectional type which consisted of 556 individuals (268 males and 288 females). Foot dimensions (foot length and foot breadth) were measured in centimeter and the foot index was derived for both sexes separately. The data was analyzed using descriptive statistics with SPSS vesion 20.0. Results: It was concluded that there were gender differences in foot length and breadth. The foot length and foot breadth were found to be higher among males than females. The bilateral differences of foot dimensions were not recorded in both male and female. There were gender differences in foot index. Conclusions: The male is found having longer and broader foot than female foot. The foot index is not used as an appropriate tool to determine gender.